2017
DOI: 10.4048/jbc.2017.20.3.310
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Germline Mutation inBRCA1Causes Exon 20 Skipping in a Korean Family with a History of Breast Cancer

Abstract: Germline mutations in the BRCA1 and BRCA2 genes are strong genetic factors for predispositions to breast, ovarian, and other related cancers. This report describes a family with a history of breast and ovarian cancers that harbored a novel BRCA1 germline mutation. A single nucleotide deletion in intron 20, namely c.5332+4delA, was detected in a 43-year-old patient with breast cancer. This mutation led to the skipping of exon 20, which in turn resulted in the production of a truncated BRCA1 protein that was 177… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Further studies demonstrated this variant segregates with breast and ovarian cancer in the family. Experimental studies showed exon skipping similar to our observations, and a functionally impaired protein [27]. BRCA1 mutation carriers are typically diagnosed with high grade, early-onset, triple-negative breast cancers (TNBC) [28, 29] and morphological features can be useful in interpreting variants [30]; however, cases of early-onset breast cancer that are not TNBC have been reported.…”
Section: Discussionsupporting
confidence: 78%
“…Further studies demonstrated this variant segregates with breast and ovarian cancer in the family. Experimental studies showed exon skipping similar to our observations, and a functionally impaired protein [27]. BRCA1 mutation carriers are typically diagnosed with high grade, early-onset, triple-negative breast cancers (TNBC) [28, 29] and morphological features can be useful in interpreting variants [30]; however, cases of early-onset breast cancer that are not TNBC have been reported.…”
Section: Discussionsupporting
confidence: 78%
“…The proband's grandfather died of lung cancer and the grandmother died of ovarian cancer at 77 years old (Figure 2). Splicing variants in BRCT domains of BRCA1 have been reported to be associated with aberrant splicing in patients with breast/ovarian cancer 27,57 . This variant does not have frequency information in genome databases, including ExAC (http://exac.broadinstitute.org/) and gnomAD (http://gnomad.broadinstitue.org), and has not been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Current enrichment methods for this gene mostly include direct amplification or hybridization capture of select short gene fragments of the coding regions ( Supplementary Table S4 ). Nevertheless, it was shown that mutations in non-coding regions of this gene can induce significant reduction of transcription ( 24 ), or exon skipping resulting in truncated BRCA1 protein ( 25 ). Furthermore, the CATCH scheme reported here is immune to genetic complexities in the target region.…”
Section: Discussionmentioning
confidence: 99%